Psychological potential of personal self-realization - Maksimenko, Sergiy; Serdiuk, Liudmyla (Social Welfare: Interdisciplinary Approach, 2016)
The article reveals the psychological foundations of the self-realization phenomenon. It shows that personal self-realization as a self-determined phenomenon is determined by a complex of interconnected personal indicators, including the value of self-development, integral perception of a personal life course, self-acceptance and so on. Psychological meaning of personal self-realization is defined, namely: psychological aspects of self-actualization that support understanding of personal meaning of self-realization. Importance to study objective laws of the process of personal self-realization through its value-semantic mediation is substantiated. An important factor of personal self-realization is internal motivation, caused by personal creativity, self-guidance, desires for self-development, a high-status position in social contact, knowledge.
Keywords: self-realization; motivation; synergy; self-determination; self-organization